Performance Analysis of Speed Controller for 3hp and 150hp Three Phase Induction Motors Being Used in Cable Industry Applications - Sathishkumar, H.; Parthasarathy, S. S. (Asian Journal of Electrical Sciences, 2019)
In this paper, Performance analysis of speed controller for 3hp and 150hp three phase induction motors being used in cable industry applications is carried out. For this purpose, cable manufacturing industry (Ravicab Cables Private Limited) at Bidadi, Ramanagara district is taken into study. A 3hp 3Φ induction motor is used to pull the single core cable which comes out of diameter controller. Similarly, a 150hp 3Φ induction motor is used to pull the four single core cable to form a four core cable. Therefore, as far as this cable industry is concerned, these motors speed control is essential. If the speed of these motors is not controlled precisely, then these motors will run at a speed which is deviated from reference speed. Hence, single and four core cable manufacturing is discussed here. Moreover, performance of speed controller (PID) which is currently existing in this industry for 3hp and 150 hp 3Φ induction motor is analysed and various controllers are proposed (Fuzzy, Neural network, Neuro-fuzzy). Eventually, robust controller for 3hp and 150hp motors is identified using comparative performance analysis between various controllers.